Quinine-Induced Disseminated Intravascular Coagulation - Firas Abed; Ramkaji Baniya; Ghassan Bachuwa (Case Reports in Medicine, 2016)
Every drug comes with some side effect. It is the benefit/risk ratio that determines the medical use of the drug. Quinine, a known antimalarial drug, has been used for nocturnal leg cramps since the 1930s; it is associated with severe life-threatening hematological and cardiovascular side effects. Disseminated intravascular coagulation (DIC), albeit rare, is a known coagulopathy associated with Quinine. It is imperative to inquire about the Quinine intake in medication history in patients with coagulopathy, as most patients still consider it a harmless home remedy for nocturnal leg cramps. In this report, we present a case of coagulopathy in a middle-aged woman, who gave a history of taking Quinine for nocturnal leg cramps, as her home remedy. Early identification of the offending agent led to the diagnosis, prompt discontinuation of the medication, and complete recovery and prevented the future possibility of recurrence.